LICENSING IN THE FRAMEWORK OF URBAN PLANNING: LAW AGAINST THE GOVERNMENT - Fitriany, Shafyra Amalia (Universitas Airlangga, 2025)
In the context of urban planning, licensing play a very important role as a tool to regulate development activities in a particular area. The state holds authority over the wealth of natural resources, including land, which is then managed by the government. The government, wielding this authority, needs to be restrained because its actions can have legal consequences. This article elucidates how permits are regulated by the law and the legal ramifications for the government. It adopts a normative juridical approach focusing on the use of literature or secondary data. The specification utilized is analytical-descriptive. The article addresses two main questions: 1) In safeguarding the public against government actions, the law must function by providing justice, legal certainty, and utility. This also involves the emergence of preventive and repressive legal protection. 2) In terms of urban planning, especially licensing,, if discrepancies arise, administrative law should take precedence to ensure compliance with jurisdictional boundaries up to its procedural regulations. Keywords: Government Actions, Legal Consequences, Legal Protection, Licensing, Urban Planning.